Influence of the Addition of Potato, Okara, and Konjac Flours on Antioxidant Activity, Digestibility, and Quality of Dumpling Wrappers - Yongli Jiang; Yimeng Zhao; Danfeng Wang; Yun Deng (Journal of Food Quality)
To improve the antioxidant activity (AA), digestibility, and quality of fiber-rich dumpling wrappers, potato, okara, and konjac flours were added to wheat flour. The contents of these additional ingredients in the dumpling wrapper were optimized using the response surface methodology and the synthetic evaluation method. The dietary fiber content (DFC) and AA of blend flours and the optimized cooking time (OCT), cooking loss (CL), hardness, chewiness, firmness, color, and sensory evaluation (SE) of dumpling wrappers were evaluated as response quality parameters. The optimized flour was identified containing 17.5 g of potato flour, 8.5 g of okara flour, and 1.2 g of konjac flour per 100 g of blend flour, which resulted in a higher synthetic evaluation index value (0.71 compared with 0.68 for wheat flour). The qualities of the optimized flour dumpling wrappers were compared with those of wheat flour dumpling wrappers to verify the practicality of the optimized flour. The results showed that the optimized flour showed better comprehensive qualities, especially regarding DFC (9.59%, fourfold higher than that of wheat flour) and AA. Furthermore, the predicted glycemic index (GI) of the optimized flour (74.93%) was lower than that of the wheat flour (81.47%). Overall, the addition of potato, okara, and konjac flours can significantly (P<0.05) improve DFC, AA, and digestibility of wheat flour. The optimized flour not only maintains excellent dumpling wrapper quality but also increases the utilization of potato and okara flours, which has great potential for industrial applications.